Flood Disaster Relief Operation: A Systematic Literature Review - Febrina; Runtuk, Johan K.; Maukar, Anastasia L.; Puspitarini, Erri W. (Jurnal Sistem Teknik Industri, 2022)
A flood is natural disaster that often occurs in many regions. Flood has a significant impact on the nature conditions, local communities, and regional economic losses. The flood can happen due to a damaged environmental system; therefore, it needs deeper study and extra effort to prevent it. Thus, an appropriate and right Disaster Relief Operation (DRO) is needed in responding to flood disaster. In this research, 50 articles categorized in "flood disaster relief operation" published in the range 2012 to 2022 have been reviewed. This review is conducted by using the Systematic Literature Review (SLR) method. This study aims to explore and analyze flood DRO. The findings reveal that the flood DRO still has several weaknesses in the current system that should be improved: the lack of an integrated information system, not enough collaboration of the stakeholders, the lateness of information exchange, and unplanned relief operations through the preparation. For further research, it is recommended to implement the proposed system in the relief operations execution.